Pembentukan Kecerdasan Emosional Melalui Pendekatan Sa`Adah Mutawazinah Di Sekolah - Nurhayati, R; Al Amin, Al Amin; Qadrianti, Laeli; Islamiah, Nurul; Ramadani, Nuriya; Nuraeni, Nuraeni; Wahdania, Wahdania (Al-Qalam: Jurnal Kajian Islam dan Pendidikan, 2024)
Emotional intelligence is an individual's potential to improve the individual's emotions. Meanwhile sa`adah mutawazinah is an approach to counselling that involves a balance between the world and the hereafter in an individual's life. The formation of emotional intelligence through the sa'adah mutawazinah approach in schools not only provides students with a deep understanding of the emotions of themselves and others, but also has a significant impact in strengthening the balance between aspects of the world and the hereafter. This article aims to determine the formation of emotional intelligence through the sa approach. `There is mutawazinah at school. This article is included in the library study. Data collection techniques are through books, journals and other documents. The results obtained are that with the sa'adah mutawazinah approach in schools, emotional intelligence is emphasized to achieve harmony between happiness in this world and the hereafter. This education emphasizes Islamic values, including empathy and self-control. The key to success lies in the integration of Islamic principles, the development of emotional values, and parental involvement, paving the way for sustainable happiness in this world and the hereafter.